Micro-RNAs: The new potential biomarkers in cancer diagnosis, prognosis and cancer therapy - Mansoori, B; Mohammadi, A; Shirjang, S; Baradaran, B (Cellular and Molecular Biology, 2015)
MicroRNAs (miRNAs) are a large class of small noncoding RNAs approximately 22 nucleotides in length. They are the main regulators of gene expression, regulating specific oncogenes, tumor suppressors, cancer stem cells and metastasis. MicroRNAs have become valuable to cancer research in recent years. They appear as a significant biomarker in tumorigenesis. Briefly, the capacities of miRNA to identify between tumor and normal tissue, to distinguish between various subgroups of tumors and to foretell results or responses to therapy have attracted scientist's attention to these small RNAs. MicroRNAs' remarkable stability in both the tissue and bloodstream of cancer patients has elevated the possibility that miRNAs may prove to be a novel diagnostic biomarker. This review focuses on the utility of miRNAs as key biomarkers in cancer diagnosis, cancer prognosis and cancer therapy.